A degradable antibacterial film and preparation method thereof
By adding clove essential oil to the blended material of chitosan and polyvinyl alcohol, a degradable antibacterial film was prepared, which solved the problems of low degradation rate of existing films, which was not resistant to high temperatures and non-anti-bacteriality, and achieved a high-performance and environmentally friendly food packaging film.
Patent Information
- Application Number
- CN202211353770.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-01
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-11-01
AI Technical Summary
The existing films have low degradation rate, are not resistant to high temperatures and are not antibacterial, which cannot effectively solve the preservation and environmental protection problems of food packaging.
A degradable antibacterial membrane is prepared by adding clove essential oil to the blend material of chitosan and polyvinyl alcohol. The method of preparing the film includes placing a chitosan acetic acid solution and a polyvinyl alcohol aqueous solution, mixing and adding glycerin, Tween-80 and clove essential oil, and then ultrasonic degassing and casting drying.
The preparation of a degradable antibacterial membrane has been achieved, with good tensile strength, elongation of break, water vapor transmittance and antibacterial properties, and has low production cost, environmentally friendly and non-toxic.
Smart Images

Figure CN115894992B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of food packaging material technology, and more specifically to a degradable antibacterial film and a preparation method thereof, which are used for food packaging and preservation. Background Art
[0002] Film is one of the most commonly used packaging materials, mainly from fossil resources. Although it is widely used in the packaging field, it also produces a large amount of solid waste, seriously polluting the environment. With the development of material technology, biodegradable packaging materials can replace some films. On the basis of meeting the requirements of good mechanical properties and barrier properties of packaging, they also have the characteristics of antibacterial, high temperature resistance and environmental protection. They are particularly suitable for food and drug packaging, and have become a hot spot in the research field of green and environmentally friendly new functional packaging materials.
[0003] Chitosan (CS) is a new type of biomaterial with excellent properties such as good biocompatibility, degradability, non-toxicity, odorlessness, and good embedding properties. Therefore, CS has wide application value in food, environmental protection, medicine and other fields.
[0004] Polyvinyl alcohol (PVA) is a water-soluble polyhydroxy polymer that is completely biodegradable. It is widely used due to its non-toxicity, harmlessness, chemical stability, good biocompatibility, low cost and good film-forming properties.
[0005] Polymer blending is one of the important means to improve polymer performance. Through blending, the purpose of improving application performance, improving processing performance or reducing costs can be achieved. By using the polymer blending method, PVA is introduced into CS to improve the orientation and crystallinity of the film and improve its mechanical properties; the biological properties of CS are used to improve the biocompatibility of PVA, and the excellent physical and mechanical properties of PVA are used to improve the problem of CS film being too brittle, so that the two can complement each other's advantages.
[0006] Clove oil (CO) is a natural essential oil, and its active ingredient is eugenol. Currently, many reports have confirmed that the volatile oil contained in clove has good antibacterial and antioxidant properties, and is a natural antioxidant and antibacterial agent. It has been proven that it has antibacterial and antioxidant activities in the liquid phase and antibacterial activity in the gas phase. The purpose of the present invention is to develop an active packaging film by adding clove oil to CS-PVA polymer, and to study its structure, mechanical and physical properties. Summary of the invention
[0007] The purpose of the present invention is to solve the technical problems of low degradation rate, high temperature resistance and non-antibacterial properties of existing films. The present invention provides a degradable antibacterial film and a preparation method thereof.
[0008] The technical solution adopted by the present invention is as follows: A method for preparing a degradable antibacterial film comprises the following steps:
[0009] S1. Prepare chitosan acetic acid solution: weigh a certain amount of chitosan powder and dissolve it in 1% glacial acetic acid solution, place the solution in a constant temperature water bath at 55°C-65°C, heat at constant temperature and stir continuously for 30 minutes until the solution is completely dissolved, to obtain a chitosan acetic acid solution with a chitosan mass concentration of 0.5%-2.5%;
[0010] S2. Prepare a polyvinyl alcohol aqueous solution: weigh a certain amount of polyvinyl alcohol crystals and add them into distilled water, heat to 90°C-99°C and stir continuously for 2 hours until completely dissolved, to obtain a polyvinyl alcohol aqueous solution with a polyvinyl alcohol mass concentration of 8%-12%;
[0011] S3, preparation of mixed solution: the chitosan acetic acid solution obtained in steps S1 and S2 is mixed with a polyvinyl alcohol aqueous solution in a mass ratio of 2:8 to obtain a composite film liquid, and the mixture is stirred evenly until transparent to obtain a composite gel, and then glycerol and Tween-80 are added and stirred for 30 minutes. After the solution becomes transparent, clove essential oil is added during stirring and stirred evenly, the prepared solution is ultrasonically degassed for 20-30 minutes, the degassed film-forming liquid is poured into a glass container to be evenly cast, and then dried in an oven at 40° C. for 24 hours to form a film. After complete drying, the composite film is peeled off to obtain a degradable antibacterial film.
[0012] Preferably, the mass concentration of chitosan is 1.5%, the mass concentration of polyvinyl alcohol is 10%, the mass concentration of glycerol is 1.5%, and the mass ratio of chitosan acetic acid solution to polyvinyl alcohol aqueous solution is controlled to be 2:8, the mass concentration of Tween-80 is 0.3%, the drying temperature is 40° C., and the mass concentration of clove essential oil in the composite membrane liquid is 0.25%-1.25%.
[0013] More preferably, the mass concentration of the clove essential oil in the composite membrane liquid is 0.75%.
[0014] Preferably, the mass concentration of chitosan is 1.5%, the mass concentration of polyvinyl alcohol is 10%, the mass concentration of clove essential oil is 0.75%, and the mass ratio of chitosan acetic acid solution to polyvinyl alcohol aqueous solution is controlled to be 8:2, the amount of Tween-80 added is 0.3%, the drying temperature is 40°C, and the mass concentration of glycerol in the composite membrane liquid is 0.5%-2.5%.
[0015] More preferably, the mass concentration of the glycerol in the composite membrane solution is 1.5%.
[0016] Preferably, the chitosan acetic acid solution is a chitosan acetic acid solution having a chitosan mass concentration of 1.5%.
[0017] Preferably, the polyvinyl alcohol aqueous solution is a polyvinyl alcohol aqueous solution with a polyvinyl alcohol mass concentration of 10%.
[0018] Preferably, the mass concentration of Tween-80 in the composite membrane solution is 0.3%.
[0019] Preferably, the stirring speed in steps S1 and S2 is 600 rpm / s.
[0020] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0021] 1. The present invention adopts chitosan and polyvinyl alcohol as film-forming substrates, glycerol as a plasticizer, clove essential oil as an antibacterial active substance, and Tween-80 as an emulsifier to prepare a degradable antibacterial film through co-dissolution; the present invention prepares the composite antibacterial preservative film from the above materials, which is non-toxic, pollution-free and degradable; and the preparation method is simple, and only simple mixing and dispersing, casting and film scraping are required, and the production cost is low.
[0022] 2. The preparation method of the degradable antibacterial film of the present invention is based on the screened film-making method, and the concentrations of chitosan, polyvinyl alcohol, clove essential oil, and glycerol are screened to make the tensile strength (TS), elongation at break (ER), water vapor permeability (WVP), hygroscopicity, and water solubility of the degradable antibacterial film optimal.
[0023] 3. The optimal preparation process was determined through response surface process optimization. The results showed that the process parameters were: chitosan addition amount was 1.5%, polyvinyl alcohol addition amount was 11%, clove essential oil addition amount was 0.75%, and glycerol addition amount was 1.5%. Under this condition, the average tensile strength of the composite film was (25.721±0.157) MPa, and the elongation at break was (295.123±4.5)%, indicating that the fitting model is feasible. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention will now be described by way of example with reference to the accompanying drawings, in which:
[0025] Figure 1 It is a process flow chart of the present invention;
[0026] Figure 2 is a response surface diagram of the interaction term of the present invention to the tensile strength;
[0027] Figure 3 is the response surface diagram of the interaction term of the present invention to the elongation at break;
[0028] Figure 4 The surface electron micrograph (1000 times magnified plane electron micrograph) and cross-sectional electron micrograph (2000 times magnified plane electron micrograph) of the antibacterial film prepared in the embodiment of the present invention are shown in FIG.
[0029] Figure 5 The infrared spectra of the antibacterial films and clove essential oil with different addition amounts of clove essential oil in the embodiments of the present invention, wherein A is a CS-PVA film; B is a CS-PVA-CO (0.5%) composite film; C is a CS-PVA-CO (0.75%) composite film; D is a CS-PVA-CO (1.0%) composite film; and E is CO. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.
[0031] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] like Figure 1-5 As shown, this embodiment provides a method for preparing a degradable antibacterial film, comprising the following steps:
[0034] S1. Prepare chitosan acetic acid solution: weigh a certain amount of chitosan powder and dissolve it in 1% glacial acetic acid solution, place the solution in a 60°C constant temperature water bath, heat at a constant temperature and stir continuously at 600 rpm / s for 30 min until it is completely dissolved, to obtain a chitosan acetic acid solution with a chitosan mass concentration of 0.5%-2.5%;
[0035] S2. Prepare a polyvinyl alcohol aqueous solution: weigh a certain amount of polyvinyl alcohol crystals, add them into distilled water, heat to 95°C, and stir continuously at 600 rpm / s for 2 hours until they are completely dissolved, to prepare a polyvinyl alcohol aqueous solution; the polyvinyl alcohol aqueous solution uses a polyvinyl alcohol aqueous solution with a polyvinyl alcohol mass concentration of 10%;
[0036] S3, preparation of mixed solution: the chitosan acetic acid solution obtained in steps S1 and S2 is mixed with a polyvinyl alcohol aqueous solution in a mass ratio of 2:8 to obtain a composite film liquid, and the mixture is stirred evenly until transparent to obtain a composite gel, 1.5% glycerol, 0.3% Tween-80, and 0.75% clove essential oil are added to the composite film liquid with mass concentrations of respectively 1.5% and 0.75%, and the mixture is stirred evenly, the prepared solution is ultrasonically degassed for 20-30 min, the degassed film-forming liquid is poured into a 23*32 cm glass container, and the film is evenly cast, and then dried in an oven at 40° C. for 24 hours to form a film, and after complete drying, the composite film is peeled off and stored in an environment with a certain temperature and relative humidity.
[0037] Experimental Example 1
[0038] The addition amount of polyvinyl alcohol was set to 10%, the addition amount of clove essential oil was set to 0.75%, and the addition amount of glycerol was set to 1.5%. At the same time, the mass ratio of PVA:CS was controlled to 8:2, the addition amount of Tween-80 was set to 0.3%, and the drying temperature was set to 40°C. When the addition amount of chitosan was set to 0.5%, 1.0%, 1.5%, 2.0%, and 2.5%, the effect of chitosan addition on the mechanical properties, water vapor permeability, and water resistance of the composite film was investigated.
[0039] Table 1. Effect of chitosan addition on composite membrane performance
[0040]
[0041] Note: Different letters in the same column indicate significant differences (P<0.05)
[0042] From the data results in Table 1, it can be seen that with the increase of chitosan addition, the tensile strength of the composite film gradually increases, and the elongation at break first increases and then decreases; at 1.5%-2.0%, the mechanical properties are good and do not change much, which is due to the large number of ring structures in the chitosan molecular chain, and the presence of a large number of hydroxyl and amino groups on the ring structure; the increase in chitosan content enhances the molecular force between the hydroxyl and amino groups in the chitosan molecule, and enhances the mechanical properties of the membrane. The water vapor permeability coefficient of the membrane decreases with the increase of chitosan concentration, because the formed composite film is more dense and water vapor is difficult to pass through. Since polyvinyl alcohol and chitosan are hydrophilic polymer materials, the composite membrane has a certain hygroscopicity. The hygroscopicity of the membrane does not change much when the chitosan addition is less than 1.5%. The water solubility of the membrane reaches the maximum when the chitosan addition is 2.0%, and its water solubility is as high as 12.02%. As the amount of chitosan added continued to increase, the hygroscopicity of the film gradually decreased. This may be because the hydroxyl and amino groups in the chitosan molecular chain formed stronger hydroxyl groups with the hydroxyl groups in polyvinyl alcohol, making the structure of the film more compact and enhancing the water resistance of the composite film. In general, the comprehensive performance of the film was the best when the chitosan addition was 1.5%.
[0043] Example 2
[0044] A method for preparing a degradable antibacterial film comprises the following steps:
[0045] S1. Prepare chitosan acetic acid solution: weigh a certain amount of chitosan powder and dissolve it in 1% glacial acetic acid solution. Place the solution in a 60°C constant temperature water bath, heat at a constant temperature and stir continuously at 600 rpm / s for 30 min until the solution is completely dissolved, to obtain a chitosan acetic acid solution with a chitosan mass concentration of 1.5%;
[0046] S2. Prepare a polyvinyl alcohol aqueous solution: weigh a certain amount of polyvinyl alcohol crystals, add them into distilled water, heat to 95°C, and stir continuously at 600 rpm / s for 2 hours until they are completely dissolved, to prepare a polyvinyl alcohol aqueous solution; the polyvinyl alcohol aqueous solution uses a polyvinyl alcohol aqueous solution with a polyvinyl alcohol mass concentration of 8%-10%;
[0047] S3, preparation of mixed solution: the chitosan acetic acid solution obtained in steps S1 and S2 is mixed with a polyvinyl alcohol aqueous solution in a mass ratio of 2:8 to obtain a composite film liquid, and the mixture is stirred evenly until transparent to obtain a composite gel, 1.5% glycerol, 0.3% Tween-80, and 0.75% clove essential oil are added to the composite film liquid with mass concentrations of respectively 1.5% and 0.75%, and the mixture is stirred evenly, the prepared solution is ultrasonically degassed for 20-30 min, the degassed film-forming liquid is poured into a 23*32 cm glass container, and the film is evenly cast, and then dried in an oven at 40° C. for 24 hours to form a film, and after complete drying, the composite film is peeled off and stored in an environment with a certain temperature and relative humidity.
[0048] Experimental Example 2
[0049] The chitosan addition amount was set to 1.5%, the clove essential oil addition amount was set to 0.75%, the glycerol addition amount was set to 1.5%, the PVA:CS mass ratio was controlled to 8:2, the Tween-80 addition amount was set to 0.3%, and the drying temperature was set to 40°C. When the polyvinyl alcohol addition amount was set to 8%, 9%, 10%, 11%, and 12%, the effect of the polyvinyl alcohol addition amount on the mechanical properties, water vapor permeability, and water resistance of the composite film was investigated.
[0050] Table 2. Effect of polyvinyl alcohol addition on composite film properties
[0051]
[0052]
[0053] Note: Different letters in the same column indicate significant differences (P<0.05)
[0054] From the data results in Table 2, it can be seen that the tensile strength and elongation at break of the composite film generally show a trend of first increasing and then decreasing with the addition of polyvinyl alcohol; as the addition of polyvinyl alcohol increases from 8% to 10%, the mechanical properties of the film continue to increase. When the addition of polyvinyl alcohol is 10%, the tensile strength and elongation at break reach 24.72MPa and 307.57%, respectively. This is because the interaction between polyvinyl alcohol and chitosan and clove essential oil molecules is enhanced, making the structure of the film more dense, but the addition of polyvinyl alcohol also limits the interaction between chitosan molecules; the water vapor permeability of the film shows a trend of first decreasing and then increasing, and is lowest when the addition is 9%-10%; polyvinyl alcohol, as a hydrophilic material, has little effect on the hygroscopicity of the film when the addition is 8%-10%, and continued addition will increase the hygroscopicity of the film; the water solubility decreases with the increase of the addition of polyvinyl alcohol, and the evaluation of various factors and indicators is comprehensive, so the addition of polyvinyl alcohol is selected as 10%.
[0055] Example 3
[0056] A method for preparing a degradable antibacterial film comprises the following steps:
[0057] S1. Prepare chitosan acetic acid solution: weigh a certain amount of chitosan powder and dissolve it in 1% glacial acetic acid solution. Place the solution in a 60°C constant temperature water bath, heat at a constant temperature and stir continuously at 600 rpm / s for 30 min until the solution is completely dissolved, to obtain a chitosan acetic acid solution with a chitosan mass concentration of 1.5%;
[0058] S2. Prepare a polyvinyl alcohol aqueous solution: weigh a certain amount of polyvinyl alcohol crystals, add them into distilled water, heat to 95°C, and stir continuously at 600 rpm / s for 2 hours until they are completely dissolved, to prepare a polyvinyl alcohol aqueous solution; the polyvinyl alcohol aqueous solution uses a polyvinyl alcohol aqueous solution with a polyvinyl alcohol mass concentration of 10%;
[0059] S3, preparation of mixed solution: the chitosan acetic acid solution obtained in steps S1 and S2 is mixed with a polyvinyl alcohol aqueous solution at a mass ratio of 2:8 to obtain a composite film liquid, and the mixture is stirred evenly until transparent to obtain a composite gel, 0.5%-2.5% of glycerol, 0.3% of Tween-80, and 0.75% of clove essential oil are added to the composite film liquid and stirred evenly, the prepared solution is ultrasonically degassed for 20-30 minutes, the degassed film-forming liquid is poured into a 23*32 cm glass container to be evenly cast, and then dried in an oven at 40° C. for 24 hours to form a film, and after complete drying, the composite film is peeled off and stored in an environment with a certain temperature and relative humidity.
[0060] Experimental Example 3
[0061] The chitosan addition amount was set to 1.5%, the polyvinyl alcohol addition amount was set to 10%, the clove essential oil addition amount was set to 0.75%, the PVA:CS mass ratio was controlled to 8:2, the Tween-80 addition amount was set to 0.3%, and the drying temperature was set to 40°C. When the glycerol addition amount was set to 0.5%, 1.0%, 1.5%, 2.0%, and 2.5%, the effect of glycerol addition amount on the mechanical properties, water vapor permeability, and water resistance of the composite film was investigated.
[0062] Table 3. Effect of glycerol addition on composite membrane performance
[0063]
[0064] From the data results in Table 3, it can be seen that with the increase of glycerol addition, the tensile strength of the composite film decreases significantly. When the addition amount increases from 0.5% to 2.5%, the tensile strength decreases from 31.74MPa to 16.92MPa. The elongation at break increases gradually; it may be that glycerol weakens the intermolecular forces of the polymer, increases the gaps between the molecules, and reduces the probability of hydrogen bonds between the polymer molecules, resulting in the relaxation and extension of the antibacterial film structure, thereby improving the flexibility and increasing the elongation at break of the composite film with the increase of glycerol addition. The hygroscopicity and water solubility of the film increase with the increase of glycerol addition, which may be because glycerol is a hydrophilic substance. Some hydrophilic groups in the blended polymer will form hydrogen bonds with the hydrophilic groups of glycerol, resulting in the enhancement of the hydrophilicity of the composite film, thereby making the entire membrane system loose and the density poor. At the same time, glycerol, which is hydrophilic, will absorb external moisture. The increase in the amount of glycerol added also increases the expansion rate of water vapor in the composite membrane, so the water vapor permeability also begins to increase after reaching a certain value. Overall, the comprehensive performance is best when the amount of glycerol added is between 1.0% and 1.5%. Considering that the mechanical properties are the best, the glycerol addition amount is selected to be 1.5%.
[0065] Example 4
[0066] A method for preparing a degradable antibacterial film comprises the following steps:
[0067] S1. Prepare chitosan acetic acid solution: weigh a certain amount of chitosan powder and dissolve it in 1% glacial acetic acid solution. Place the solution in a 60°C constant temperature water bath, heat at a constant temperature and stir continuously at 600 rpm / s for 30 min until the solution is completely dissolved, to obtain a chitosan acetic acid solution with a chitosan mass concentration of 1.5%;
[0068] S2. Prepare a polyvinyl alcohol aqueous solution: weigh a certain amount of polyvinyl alcohol crystals, add them into distilled water, heat to 95°C, and stir continuously at 600 rpm / s for 2 hours until they are completely dissolved, to prepare a polyvinyl alcohol aqueous solution; the polyvinyl alcohol aqueous solution uses a polyvinyl alcohol aqueous solution with a polyvinyl alcohol mass concentration of 10%;
[0069] S3, preparation of mixed solution: the chitosan acetic acid solution obtained in steps S1 and S2 is mixed with a polyvinyl alcohol aqueous solution in a mass ratio of 2:8 to obtain a composite film liquid, and the mixture is stirred evenly until transparent to obtain a composite gel, 1.5% glycerol, 0.3% Tween-80, and 0.25%-1.25% clove essential oil are added to the composite film liquid and stirred evenly, the prepared solution is ultrasonically degassed for 20-30 minutes, the degassed film-forming liquid is poured into a 23*32 cm glass container, and the film is evenly cast, and then dried in an oven at 40° C. for 24 hours to form a film, and after complete drying, the composite film is peeled off and stored in an environment with a certain temperature and relative humidity.
[0070] Experimental Example 4
[0071] The chitosan addition amount was set to 1.5%, the polyvinyl alcohol addition amount was set to 10%, the glycerol addition amount was set to 1.5%, the PVA:CS mass ratio was controlled to 8:2, the Tween-80 addition amount was set to 0.3%, and the drying temperature was set to 40°C. When the clove essential oil addition amount was set to 0.25%, 0.50%, 0.75%, 1.00%, and 1.25%, the effect of the clove essential oil addition amount on the mechanical properties, water vapor permeability, and water resistance of the composite film was investigated.
[0072] Table 4. Effect of clove essential oil addition on composite film properties
[0073]
[0074] From the data in Table 4, it can be seen that with the addition of clove essential oil, the tensile strength of the film decreases, but the elongation at break increases. This may be because the addition of clove essential oil partially replaces the strong interaction between chitosan and polyvinyl alcohol molecules. The addition of essential oil forms a discontinuous non-homogeneous film structure. These discontinuities lead to a decrease in the film's resistance to damage and an increase in elongation at break. The water vapor permeability of the film decreases first and then increases with the increase in the amount of clove essential oil added. When the addition amount is 0.75%, the water vapor permeability of the film is 0.479 g·mm·m -2 ·h -1 kPa -1. It can be attributed to the fact that the addition of essential oil increases the hydrophobicity and bending coefficient of the membrane, thereby limiting the absorption of water molecules and their movement rate in the membrane network structure, which ultimately leads to a decrease in the water vapor permeability of the membrane. When the content of clove essential oil in the membrane is greater than 0.75%, the water vapor permeability of the membrane gradually increases. This is because too much essential oil makes the membrane structure loose, and the gap between polymers increases, resulting in discontinuity of the membrane structure. The hygroscopicity of the membrane shows a trend of first decreasing and then increasing. With the increase in the amount of clove essential oil added, the water solubility of the membrane continues to decrease; until the addition amount is 0.75%, the water solubility of the membrane reaches the lowest, indicating that the addition of clove essential oil can enhance the waterproof performance of the membrane; and when a high content of clove essential oil is added to the membrane, the continuous structure of the membrane is destroyed and becomes loose, which is more soluble in water and increases the water solubility. Therefore, it is best to choose 0.75% clove essential oil.
[0075] Analysis example
[0076] 1. Analysis of response surface test results
[0077] like Figure 2-3 As shown in the figure, the Design Expert 8 software was used for analysis to obtain the optimal preparation process of the composite film. Taking the highest values of tensile strength and elongation at break as the standard, the optimal set of component ratios was obtained. At this time, the process conditions were chitosan addition of 1.56%, polyvinyl alcohol addition of 10.9%, glycerol addition of 1.56%, and clove essential oil addition of 0.81%. The software predicted tensile strength of 25.6891MPa and elongation at break of 292.95%.
[0078] A verification test was carried out based on the best set of parameters in the software analysis results. In actual operation, the process conditions were set to 1.56% chitosan addition, 10.9% polyvinyl alcohol addition, 1.56% glycerol addition, and 0.81% clove essential oil addition. The tensile strength and elongation at break of the composite film were measured. The test was repeated three times. Under this condition, the average tensile value of the composite film was 25.72±0.15MPa, and the elongation at break was 295.12%±4.50%, which were close to the theoretical predicted values, indicating that the fitting model is feasible and the experiment is meaningful.
[0079] 2. Scanning electron microscopy analysis
[0080] like Figure 4 As shown, using a scanning electron microscope, the structure of the composite film at the micron scale can be seen. By observing whether the surface of the composite film is smooth and flat, whether the cross-section and layers are arranged tightly and orderly, and the uniformity of the distribution of various components in the composite film, the effect of adding clove essential oil on the composite film is explored. Figure 4The surface and cross-section of the CS-PVA film prepared under the optimal conditions and the CS-PVA film with different concentrations of clove essential oil added under a scanning electron microscope. The pure CS-PVA surface and the pure CS-PVA cross-section are the surface and cross-section of the CS-PVA film without essential oil. It can be seen from the figure that the surface is smooth, flat, and has a non-porous structure under a 1000-fold microscope. The cross-section under 2000 times is also flat, but shows a porous structure. The CS-PVA film with clove essential oil added shows a loose structure on the surface at the same magnification, as shown in the CS-PVA-0.5% clove essential oil surface and the CS-PVA-0.5% clove essential oil cross-section. The surface and cross-section of the film containing 0.5% clove essential oil are covered with pores and look like a sponge. It is speculated that the observed changes in the structure of the composite film may be caused by the destruction of the ordered structure of the CS-PVA polymer by the clove essential oil component. As shown in the CS-PVA-0.75% clove essential oil surface and CS-PVA-0.75% clove essential oil cross section, the surface and cross section of the membrane change with the increase of clove essential oil addition. When the clove essential oil addition is 0.75%, the surface is slightly uneven except for a small number of holes, and the cross section is generally flat, without bubbles or faults, and there are no oil droplets on the surface and cross section of the membrane. The reason may be that the size of the clove essential oil is well embedded in the CS-PVA matrix, which leads to enhanced interaction between the CS-PVA matrix and the clove essential oil, making it difficult to identify the oil droplets. This shows that under the action of the surfactant Tween-80, the essential oil and the film-forming system have good compatibility. Bonilla et al. found similar results by combining essential oils into gelatin and chitosan films. When the clove essential oil addition is 1%, as shown in the CS-PVA-1% clove essential oil surface and CS-PVA-1% clove essential oil cross section, the number of oil droplets increases and becomes slightly larger. This may be attributed to the deformation force generated by the aggregation of CS-PVA chains during the film drying process. This leads to a discontinuous structure in the film matrix. It is speculated that excessive addition of clove essential oil will still destroy the ordered structure of the CS-PVA polymer, and large holes can be observed on the cross section.
[0081] 3. Fourier infrared analysis
[0082] Infrared spectroscopy uses the fact that when infrared light is irradiated on a substance, the chemical bonds or functional groups in the molecules in the substance will vibrate and absorb. Since different chemical bonds or functional groups have different absorption frequencies, it can be used to analyze whether there is interaction between molecules. Figure 5 It can be seen that the infrared spectra of pure CS-PVA film and composite films with different clove essential oil addition amounts are basically the same, with the wave number in the characteristic area being 3700-3200cm -1 The range is due to the characteristic peak caused by OH stretching vibration; at wave number 3000-2800cm -1There are two peaks in the range of 1800-1550cm, which are the stretching vibrations of saturated CH bonds in -CH3 and -CH2. -1 The absorption peak between the wave numbers is the stretching vibration of C=O. -1 The two peaks appearing at 1088cm are deformation vibrations of CH bonds or NH. -1 The characteristic peak is caused by CO stretching vibration. By comparing the infrared spectra of the four films A, B, C, and D, it can be seen that the composite film after adding clove essential oil has a peak at 3329cm -1 The vibration absorption peak at 3305 cm-1 is narrowed, and the absorption peaks of composite films B, C, and D are shifted to 3305 cm-1. -1 The wave number red shift indicates that the addition of clove essential oil will enhance the formation of hydrogen bonds within and between molecules of the CS-PVA composite film. Comparison of the infrared spectra of the four films revealed that no new peaks appeared, indicating that no chemical reaction occurred after compounding with clove essential oil. Comparison of the composite films with and without the addition of clove essential oil revealed that there was no significant change in the wave number and peak intensity of all characteristic peaks, which again shows that the addition of clove essential oil to the composite film only resulted in physical cross-linking hydrogen bonding, and also proved that the CO-CS-PVA composite film was successfully prepared.
[0083] The working principle of the present invention is as follows: the present invention uses chitosan and polyvinyl alcohol blended as film-forming substrates, glycerol as a plasticizer, clove essential oil as an antibacterial active substance, and Tween-80 as an emulsifier to prepare a degradable antibacterial film by co-dissolving. A single factor experiment was conducted with four factors, namely, chitosan addition amount (w / v), polyvinyl alcohol addition amount (w / v), glycerol addition amount (v / v), and clove essential oil addition amount (v / v); on the basis of the single factor experiment, the above four factors were selected according to the Box-Behnken central combination method, and a response surface experimental design was conducted. The DesignExpert8.06 software was used for regression analysis to explore the optimal process parameters.
Claims
1. A method for preparing a degradable antibacterial film, characterized in that: The following steps are involved: S1. Prepare chitosan acetic acid solution: weigh a certain amount of chitosan powder and dissolve it in 1% glacial acetic acid solution, place the solution in a constant temperature water bath at 55°C-65°C, heat at constant temperature and stir continuously for 30 minutes until it is completely dissolved, to obtain a chitosan acetic acid solution with a chitosan mass concentration of 1.5%; S2. Prepare polyvinyl alcohol aqueous solution: weigh a certain amount of polyvinyl alcohol crystals and add them to distilled water, heat to 90°C-99°C and stir continuously for 2 hours until it is completely dissolved, to obtain a polyvinyl alcohol aqueous solution with a polyvinyl alcohol mass concentration of 10%; S3. Prepare mixed solution: mix the chitosan acetic acid solution obtained in steps S1 and S2 with the polyvinyl alcohol aqueous solution in a mass ratio of 2:8 After mixing, a composite membrane liquid is obtained, which is stirred evenly until transparent to obtain a composite gel, and then 1.5% of glycerol and 0.3% of Tween-80 are added to the composite membrane liquid and stirred for 30 minutes. After the solution becomes transparent, 0.75% of clove essential oil is added to the composite membrane liquid during stirring, and the mixture is fully stirred. The prepared solution is ultrasonically degassed for 20-30 minutes, and the degassed film-forming liquid is poured into a glass container to be evenly cast, and then dried in an oven at 40° C. for 24 hours to form a film. After complete drying, the composite film is peeled off to obtain a degradable antibacterial film. The stirring speed of steps S1 and S2 is 600 rpm.
2. A degradable antibacterial film, characterized in that: The degradable antibacterial film is prepared by the preparation method of the degradable antibacterial film according to claim 1.